2016
DOI: 10.1111/irv.12371
|View full text |Cite
|
Sign up to set email alerts
|

Timing of influenza epidemics and vaccines in the American tropics, 2002–2008, 2011–2014

Abstract: BackgroundInfluenza‐associated illness results in increased morbidity and mortality in the Americas. These effects can be mitigated with an appropriately chosen and timed influenza vaccination campaign. To provide guidance in choosing the most suitable vaccine formulation and timing of administration, it is necessary to understand the timing of influenza seasonal epidemics.ObjectivesOur main objective was to determine whether influenza occurs in seasonal patterns in the American tropics and when these patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 11 publications
1
47
0
1
Order By: Relevance
“…Overall, the partition into three large transmission zones that was made by WHO (Central America Caribbean from Mexico in the North to Panama in the South; Tropical South America from Colombia in the North to Peru, Bolivia and Brazil in the South; and Temperate South America including Chile, Argentina, Uruguay and Paraguay) [24] does not seem fully appropriate as it overlooks some of the differences we observed (for example, between regions in Brazil and between neighbouring countries in central America). Data from the literature for countries not included in our database [20, 2527] provide further support for this view.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Overall, the partition into three large transmission zones that was made by WHO (Central America Caribbean from Mexico in the North to Panama in the South; Tropical South America from Colombia in the North to Peru, Bolivia and Brazil in the South; and Temperate South America including Chile, Argentina, Uruguay and Paraguay) [24] does not seem fully appropriate as it overlooks some of the differences we observed (for example, between regions in Brazil and between neighbouring countries in central America). Data from the literature for countries not included in our database [20, 2527] provide further support for this view.…”
Section: Discussionmentioning
confidence: 54%
“…vaccinating in April using the Southern hemisphere formulation in all countries except Mexico and Cuba) [20]. However, it is critical to note that the proportion of cases preventable with a single dose of influenza vaccine administered in April-May will vary considerably between countries and across years within the same country.…”
Section: Discussionmentioning
confidence: 99%
“…Central American countries collaborated and pooled their national antigenic characterization data into a regional analysis and confirmed that the Southern Hemisphere formulation corresponded to the most updated formulation available before the start of influenza seasons. The analysis of influenza surveillance data from 2002–2008 and 2011–2014 in the American tropics (101 y of cumulative data; 403,584 specimens tested) indicated that 13 (81%) of 16 participating countries had influenza epidemics that, on average, started during May and lasted 4 months 12 . This regional analysis was a decisive element for the policy adjustments and for developing regional TAG recommendations in July 2015 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Contrarily to countries from temperate zones such as Argentina, Chile and Uruguay, where well-defined influenza seasons have allowed for an optimal planning of vaccination, tropical countries have historically had difficulties characterizing the seasonality of influenza viruses' circulation. Three sub-regions, namely the Southern Cone, the Andean region and Central America show virus circulation that is typical of the Southern Hemisphere (peak activity mid-year) 12,15 . (Supplemental Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Between June 29 and August 9, 2016--months when influenza typically circulates in Nicaragua [4]--we approached all women who attended prenatal and postpartum visits at the German Nicaraguan Hospital, the Bertha Calderón Roque Hospital and 140 primary healthcare facilities in Managua until sample size was achieved. Women had to have been pregnant during the months of May and June and residents of the Department of Managua in order to participate in the survey.…”
Section: Methodsmentioning
confidence: 99%